2017
DOI: 10.3389/fpls.2017.02085
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of UGT716A1 as a Multi-substrate UDP:Flavonoid Glucosyltransferase Gene in Ginkgo biloba

Abstract: Ginkgo biloba L., a “living fossil” and medicinal plant, is a well-known rich source of bioactive flavonoids. The molecular mechanism underlying the biosynthesis of flavonoid glucosides, the predominant flavonoids in G. biloba, remains unclear. To better understand flavonoid glucosylation in G. biloba, we generated a transcriptomic dataset of G. biloba leaf tissue by high-throughput RNA sequencing. We identified 25 putative UDP-glycosyltransferase (UGT) unigenes that are potentially involved in the flavonoid g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 72 publications
0
25
0
Order By: Relevance
“…In the initial study of rUGT73A17 protein, we found it was capable of glucosylating epicatechin gallate as GbUGT716A1 [ 29 ], which is distinct from the other characterized UGTs. Therefore, we further identified the other flavonoid substrates of the recombinant UGT73A17 protein.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the initial study of rUGT73A17 protein, we found it was capable of glucosylating epicatechin gallate as GbUGT716A1 [ 29 ], which is distinct from the other characterized UGTs. Therefore, we further identified the other flavonoid substrates of the recombinant UGT73A17 protein.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, UGT73A17 is highly expressed in mature leaves, which is possibly responsible for the production of rutin. Although CsUGT73A17 formed 7- O -glucosides as major products and 3- O -glucosides as minor products, it is still possible that it is responsible for the biosynthesis of rutin, since in vitro activity doesn't always reflect in vivo activity as for UGT in several previous studies [ 29 , 31 , 36 , 37 ]. Taken together, these CsUGTs are most likely responsible for the accumulation of different flavonoid glucosides in different organs of tea plant.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Association of sequential enzymes and structural proteins into metabolons to facilitate metabolic channeling has been reported in plant core and specialized metabolism (Knudsen et al ., ). Group Q UGTs have shown broad activities towards phenolic substrates, and a strong preference of flavones and flavonols in vitro ( Ginkgo biloba , P. granatum and Pilosella officinarum ; Witte et al ., ; Su et al ., ; Wilson et al ., ). The physical interactions between group Q UGTs and other proteins could be explored in the future to determine the function of the surface regions of these UGTs in forming metabolons and producing flavonoid glycosides.…”
Section: Discussionmentioning
confidence: 99%
“…Ginkgo flavonoids and ginkgolides had been widely used as important drug and dietary supplements in the world (Su et al, 2017). IAA-Asp-N-glucoside was mentioned as the main pharmacological compound in ginkgo for inhibiting cough, antiasthmatic and eliminating phlegm (Liu et al, 2018);furthermore, there were considerable pharmacological studies on IAA derivates or indole alkaloids, for instance, IAA induced cell death in combination with UV-B irradiation by increasing apoptosis in PC-3 prostate cancer cells (Kim et al, 2010); indole-N-glucosides have the potential to serve as a novel SGLT2-selective inhibitors (Sodium-Glucose cotransporter) to cure type Ⅱ diabetes (Nomura et al, 2013).…”
Section: The Application Prospect Of Gbngt1mentioning
confidence: 99%